THE SYSTEMATICS OF ONLINE DEBT COLLECTION SPEECH IN INDONESIAN - Filia, Filia, Dr.; Herjoko, Muhammad Rifqi (UI Scholars Hub, 2025)
This study examines the discourse systematics used in the online loan collection speeches in the Indonesian language. Online loans are one of the financial services that are widely used by the people nowadays. However, the efforts to collect these loans have raised issues within the community. This study aims to elaborate on the speech acts and systematics forming the discourse of online loan collection. This study is using 50 screenshots of online loan collection messages on Instagram accounts as the data source. Research data is in the form of speeches used by the creditors to collect debt from the debtors. The analysis was carried out using Beller's (2005) threatening speech approach. Based on these study results, the systematics of online loan collection discourse consists of four constructions, namely (i) conditional form, (ii) conjunctive form, (iii) disjunctive form, (iv) and temporal form.